Pediatric cardiologyLess invasive percutaneous closure of persistent arterial duct in children below 10 kilos - Kusa, Jacek; Raś, Małgorzata; Cześniewicz, Paweł; Nahirny, Robert (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction: There is quite high risk of vascular complications connected with arterial puncture – mainly in the group of the smallest patients weighing less than 10 kg. Aim : To evaluate a new method of percutaneous closure of persistent arterial duct (PDA) in small children. Material and methods: Six patients were enrolled in this method of PDA closure at the age of 10.67 ±1.97 months. The mean weight was 8.85 ±0.66 kg. The occluders were implanted using only venous access. The position of the occluder was determined by angiography in the pulmonary artery through the delivery system and by echocardiography. Results : The procedure was effective in all six cases but we managed to proceed in the planned transvenous method in five cases. There was one case of complete duct constriction after introduction of the catheter, so precise measurements were impossible. After removal of the catheter the constriction remitted completely. The duct was closed in the standard manner. During echocardiographic examination we found complete closure of all six arterial ducts directly after the procedures and in the follow-up (9.17 ±3.02 months). No stenosis within the pulmonary arteries or aorta were found. Conclusions : Transcatheter arterial duct occlusion without arterial puncture is an effective and safe method of treatment allowing one to reduce the complications connected with arterial puncture. A possible complication of this method may be a constriction of the duct walls as a result of a larger amount of manipulations.